A reply to Capt. Middleton's answer to the remarks on his vindication of his conduct in a late voyage made by him in the Furnace sloop, by orders of the Lords Commissioners of the Admiralty, to find out a passage from the north-west of Hudson's Bay, to the western and southern ocean of America . [electronic resource] : to which is added, a full answer to a late pamphlet published by Capt. Middleton, called Forgery Detected. - Dobbs, Arthur, 1689-1765. (London : Printed and sold by J. Robinson ., 1745)
Electronic reproduction. Mode of access: Internet. 44